South Asia's nuclear security dilemma : India, Pakistan, and China - Dittmer, Lowell (Routledge, 2015)
The nuclear test explosions in India and Pakistan in 1998, followed by the outbreak of hostilities over Kashmir in 1999, marked a frightening new turn in the ancient, bitter enmity between the two nations. Although the tension was eclipsed by the events of 9/11 and the subsequent American attacks on Afghanistan and Iraq, it has not disappeared, as evidenced by the 2001 attack in the Indian Parliament by Islamic fundamentalists out of Kashmir. By 2002, these two nuclear-armed neighbors seemed to be once again on the brink of war. This book outlines the strategic structure of the rivalry and the.